Simultaneous detection of single‐nucleotide variant, deletion/insertion, and fusion in lung and thyroid carcinoma using cytology specimen and an RNA‐based next‐generation sequencing assay. Issue 3 (24th January 2018) - Guseva, Natalya V.; Jaber, Omar; Stence, Aaron A.; Sompallae, Krishnaveni; Bashir, Amani; Sompallae, Ramakrishna; Bossler, Aaron D.; Jensen, Chris S.; Ma, Deqin
Abstract : BACKGROUND: Molecular testing for epidermal growth factor receptor ( EGFR ) mutation and anaplastic lymphoma kinase ( ALK ) and ROS proto‐oncogene 1, receptor tyrosine kinase ( ROS1 ) fusion is routinely performed in patients with stage IV lung adenocarcinoma to assess their eligibility for targeted therapy. Fine‐needle aspiration (FNA)‐derived material frequently is the only pathologic material available. The identification of genomic aberrations in thyroid nodules from FNA smears may help stratify cancer risk and spare patients from a second surgery. In the current study, the authors tested nucleic acid extracted from the cytology smears of lung and thyroid carcinomas for simultaneous detection of single‐nucleotide variant, insertion/deletion, and gene fusion using an RNA‐based next‐generation sequencing assay. METHODS: A total of 27 cases (17 lung and 10 thyroid carcinomas, the majority of which had known variants) were tested. Areas of interest were scrapped from stained smears using a scalpel. Total nucleic acid was extracted. Gene fusion and mutational analysis was performed using the Comprehensive Thyroid and Lung FusionPlex Assay. Data were analyzed using the analysis pipeline provided by the vendor. Eleven cases with available formalin‐fixed, paraffin‐embedded (FFPE) tissue were tested in parallel. RESULTS: Gene fusions were detected in 6 cases; common single‐nucleotide variants in EGFR, RAS, and BRAF in 14 cases; and in‐frame deletions within EGFR in 3 cases. A concordance rate of 100% was observed between FNA and FFPE tissue. CONCLUSIONS: Cytology preparations can be a reliable source for the detection of both DNA and RNA aberrations. The ability to simultaneously detect multiple types of genomic variants is crucial for patients with advanced cancer and maximizes the usefulness of cytology specimens. Cancer Cytopathol 2018;126:158‐69. © 2018 American Cancer Society . Abstract : Molecular testing in patients with lung adenocarcinoma and thyroid carcinoma are used to assess their eligibility for targeted therapy and guide patient management. Cytology smear is a cost‐effective, reliable source for the detection of multiple types of genomic variants using an RNA‐based next‐generation sequencing assay. See also pages 155‐7.